Implementation of Oral Production Activities through Remote Learning: A Case Study of EFL Students at Universidad Nacional, Costa Rica - Carranza-Marchena, Priscilla (2022)
During the school year 2020, as in many other educational settings, classes at Universidad Nacional (UNA), Costa Rica, had to be rapidly transformed and adapted so that the pedagogical mediation process could be changed from the traditional face-to-face or in-class sessions to remote learning. This process, certainly, posed varied challenges in terms of the mediation process and technology-related issues, which had to be addressed efficiently in order to guarantee access to education. In this regard, this article is based on the experience lived with two groups of students taking English as a Foreign Language (EFL) in the course of English II (during the II term of 2020), at Campus Omar Dengo, Heredia, which were taught through remote learning. For this qualitative research, data were collected by means of a closed and open-ended questionnaire in which information related to the oral-production activities implemented during classes was gathered. This instrumental case study concludes with three main statements about the implementation of oral-production tasks: a) planning, b) scaffolding, and c) feedback.